GOOD CORPORATE GOVERNANCE DALAM MENINGKATKAN KINERJA KEUANGAN BANK SYARIAH - M Pudail; Yeni Fitriyani; Achmad Labib (STAI Syubbanul Wathon Magelang, 2018)
The existence of interest between principal and agent, hence arises aconflict of interest in management of Syria bank. In order to minimizethe conflict, the implementation of GCG can be one of the solutions.Implementation of GCG, which is done consistently and continuouslyin the end can improve the financial performance of sharia banks. Thetype of this study is the study of causality with quantitative approach.The number of samples in the study was 13 sharia banks withdocumentation as their data collection method. Data analysis techniquein this research is using a panel data regression method with the help ofsoftware Evies version 9. The result of this research indicates that GCGimplementation has significant influence to NPF, ROA, and BOPO.The implementation of GCG in this study proved to have no effect onROE and FDR.